Digitalizing Village Administration: A Case Study Of Cikidang Lembang - Asep Kayudin; Syifa Aulya; Novia Nurul Puspita; Dhita Ayu Amalia (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract The rapid development of digital technology has transformed governance, including administrative services at the village level, making digitalization an urgent need to improve efficiency, transparency, and community participation. This study aims to analyze the implementation of the Cikidang Lembang Village website as a medium for administrative services. The research is grounded in e-government theory, the Technology Acceptance Model (TAM), and public service quality theory (SERVQUAL), which explain the role of digital platforms in enhancing governance outcomes and citizen engagement. Using a qualitative descriptive approach with a case study method, data were collected through observation, interviews, and documentation involving village officials, residents, and student developers. The findings show that the website successfully improves administrative efficiency, reduces manual workloads, and fosters transparency through features such as online letter services, news updates, and citizen aspiration forms. However, challenges such as limited digital literacy and infrastructure remain. Overall, the study confirms that participatory approaches in system development strengthen adoption and sustainability. Keywords: Digital Governance, Village Administration, E-Government